2016
DOI: 10.1080/14756366.2016.1201479
|View full text |Cite
|
Sign up to set email alerts
|

New light on bacterial carbonic anhydrases phylogeny based on the analysis of signal peptide sequences

Abstract: Among protein families, carbonic anhydrases (CAs, EC 4.2.1.1) are metalloenzymes characterized by a common reaction mechanism in all life domains: the carbon dioxide hydration to bicarbonate and protons (CO 2 +H 2 O () HCO 3 À +H + ). Six genetically distinct CA families are known to date, the a-, b-, g-, d-, z-and Z-CAs. The last CA class was recently discovered analyzing the amino acid sequences of CAs from Plasmodia. Bacteria encode for enzymes belonging to the a-, b-, and g-CA classes and recently, phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 66 publications
1
61
0
Order By: Relevance
“…Our previous phylogenetic analysis suggested that ␤-CA genes have crossed species boundaries on multiple occasions (8). The present identification of ␤-CA genes within bacterial GIs also strongly suggests that prokaryotic ␤-CA genes have been horizontally transferred between and within different species (47). Specifically, we see what appears to be a very clear case of HGT of a ␤-CA from prokaryotic GIs to the protists T. vaginalis FIG 3 Sequence conservation analysis.…”
Section: Discussionsupporting
confidence: 58%
“…Our previous phylogenetic analysis suggested that ␤-CA genes have crossed species boundaries on multiple occasions (8). The present identification of ␤-CA genes within bacterial GIs also strongly suggests that prokaryotic ␤-CA genes have been horizontally transferred between and within different species (47). Specifically, we see what appears to be a very clear case of HGT of a ␤-CA from prokaryotic GIs to the protists T. vaginalis FIG 3 Sequence conservation analysis.…”
Section: Discussionsupporting
confidence: 58%
“…In our investigation on the bacterial CAs, it has also been noted that bor c-CA primary structures belonging to some pathogenic Gram-negative bacteria are typified by a secretory signal peptide of 18 or more amino acid residues 7,8 . These findings coupled with the evidence that also the bacterial i-CAs have a putative secretory signal peptide suggest that the b-, cand/or i-CAs characterised by the presence of a signal peptide might have in the Gram-negative bacteria a periplasmic localisation supporting or complementing the same role of the a-CAs 7,8 . Figure 3 shows the alignment of the i-CA amino acid sequences identified in B. territorii and T. pseudonana.…”
Section: Primary Sequence and Phylogenetic Analysismentioning
confidence: 76%
“…Since the CA hydratase/dehydratase activity contributes to numerous physiological functions involving dissolved inorganic carbon, CAs are crucial biomolecules in many physiological and pathological conditions in all types of organisms 6 . In the last years, and especially, to the rapid emergence of the bacterial antibiotic resistance that is occurring worldwide, the understanding of the function of bacterial CAs has increased significantly 7,8 . CAs are essential for the survival of the microbes and their pathogenicity and virulence 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes belonging to ζ-CAs classes present hydrolytic activity in ester groups, and hence P-nitrophenyl acetate hydrolysis to P-nitrophenol acetate is used as a measure of carbonic anhydrase activity. According to Supuran and Capasso (2016), genes encoding for α-CAs are present in Gram negative bacteria whereas genes encoding β-Cas and γ-Cas are found in Gram negative and Gram positive bacteria, with the exception of Helicobacter pylori, which presents encoding genes for three families (α-, β-, and ζ-CAs classes).…”
Section: Genetic Factors Involved In Enzymatic Activity (Ue and Ca) Imentioning
confidence: 99%